Individual Differences in Vicarious Pain Perception Linked to Heightened Socially Elicited Emotional States - Botan, Vanessa; Bowling, Natalie C.; Banissy, Michael J.; Critchley, Hugo; Ward, Jamie (Frontiers in Psychology, 2018)
For some people (vicarious pain responders), seeing others in pain is experienced as pain felt on their own body and this has been linked to differences in the neurocognitive mechanisms that support empathy. Given that empathy is not a unitary construct, the aim of this study was to establish which empathic traits are more pronounced in vicarious pain responders. The Vicarious Pain Questionnaire (VPQ) was used to divide participants into three groups: 1) non- responders (people who report no pain when seeing someone else experiencing physical pain), 2) sensory-localised responders (report sensory qualities and a localised feeling of pain) and 3) affective general responders (report a generalised and emotional feeling of pain). Participants completed a series of questionnaires including the Interpersonal Reactivity Index (IRI), the Empathy Quotient (EQ), the Helping Attitudes Scale (HAS), and the Emotional Contagion Scale (ECS) as well as The Individualism – Collectivism Interpersonal Assessment Inventory (ICIAI) and a self-other association task. Both groups of vicarious pain responders showed significantly greater emotional contagion and reactivity, but there was no evidence for differences in other empathic traits or self-other associations. Subsequently, the variables were grouped by a factor analysis and three main latent variables were identified. Vicarious pain responders showed greater socially elicited emotional states which included the ECS, the Emotional Reactivity Subscale of EQ and the HAS. These results show that consciously feeling the physical pain of another is mainly linked to heightened emotional contagion and reactivity which, together with HAS, load on the socially-elicited emotional states factor indicating that, in our population, these differences lead to a more helpful rather than avoidant behavior.